Presence of viable gram-positive bacteria in blood of patients with inflammatory bowel disease is not affected by treatment - Davidson, Sanna; So, Yunjeong; Oscarsson, Elin; Håkansson, Åsa ; 0000-0001-7584-5540; Sjöberg, Klas ; 0000-0002-8700-9141 (Scientific Reports, 2025)
In inflammatory bowel disease (IBD) the pathogenetic process is characterized by dysbiosis, increased permeability, translocation, and immune activation. The aim of the present study was to assess the presence of viable bacteria in the blood of patients with IBD and to correlate the findings with clinical characteristics. The study included 28 patients with Crohn’s disease (CD) (median age 38 years, 50% female, biological treatment in 71%) and 19 patients with ulcerative colitis (UC) (median age 45 years, 33% female, biological treatment in 84%). Identification of viable bacteria in the blood was evaluated by optimized cultivation and Sanger sequencing and for quantification real-time PCR was performed. Viable Gram-positive bacteria were detected in 34 IBD patients (72.3%). There were no associations between the presence of bacteria and gender, antibiotic treatment, intake of alcohol, use of PPI, steroids, or biological treatment. The number of bacterial copies was correlated with higher C-reactive protein (CRP) (p = 0.013). In ¾ of the patients, viable bacteria were identified in the blood despite treatment with biologicals, which indicates a vast barrier defect. This observation also indicates that the disease is still active. To obtain a true deep mucosal healing an intact barrier function is required.
Publisher Copyright: © The Author(s) 2025.
Keywords: Crohn’s disease; Inflammatory bowel disease; Microbiome; Permeability; Translocation; Ulcerative colitis